2003
DOI: 10.1677/jme.0.0310541
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism induces type 2 iodothyronine deiodinase expression in mouse heart and testis

Abstract: In the present study we show the expression profiles of both type 1 and type 2 iodothyronine deiodinases (D1 and D2) in a wide spectrum of mouse tissues, and D2 regulation by thyroid status. A characteristic tissue-specific expression for each isoform was observed. D2 transcripts were detected in most tissues with variable levels of expression. The observed D2 mRNA tissue distribution was similar to that described in rats and is in agreement with the view of different patterns of expression between rodents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 49 publications
6
24
1
Order By: Relevance
“…Although we detected D1, D2, and D3 mRNA in the lungs of SB animals, in agreement with previous reports (11,12), expression of D1 was lower than expression of D2 [cycle threshold (Ct) for D1, 31.3 ± 0.2; Ct for D2, 28.3 ± 0.4]. No differences in D1 and D3 mRNA levels were observed between VILI and SB WT animals ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Although we detected D1, D2, and D3 mRNA in the lungs of SB animals, in agreement with previous reports (11,12), expression of D1 was lower than expression of D2 [cycle threshold (Ct) for D1, 31.3 ± 0.2; Ct for D2, 28.3 ± 0.4]. No differences in D1 and D3 mRNA levels were observed between VILI and SB WT animals ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Until now, evidence suggesting that TH influences adult lung physiology has been indirect and based on the presence of TH receptors (8), deiodinases (9)(10)(11)(12), and measured TH concentrations (10,13,14) in the lung.…”
mentioning
confidence: 99%
“…Type 2 deiodinase expression in rodent heart is much lower than in human heart (Croteau et at., 1996), therefore rodents are not considered a suitable model for human D2 regulation. Cardiac D2 mRNA and activity in mouse and rats has, however, been demonstrated to respond to changes in thyroid hormone levels induced by hypothyroidism provoked by methimazol treatment (Wagner et al, 2003) or iodine deficiency (Lavado-Autric et al, 2013) and attenuated by T3 administration (Wagner et al, 2003). This could indicate that in our study, local changes in thyroid hormone evoked by CR were not sufficient to alter D2 expression.…”
Section: Discussioncontrasting
confidence: 55%
“…Type 2 deiodinase (D2) catalyzes T 4 to T 3 conversion, and plays a critical role in maintaining intracellular T 3 levels in specialized tissues, such as the anterior pituitary, CN, and brown adipose tissue (BAT) (1). D2 gene (DIO2) expression has also been reported in pituitary, thyroid, placenta, heart and skeletal muscle, and testis (2)(3)(4)(5)(6)(7)(8). Recently, it has been suggested that D2 also contributes for a fraction of the serum T 3 levels in euthyroid and hypothyroid individuals (9).…”
Section: Introductionmentioning
confidence: 99%